High-negative-electricity nanofiltration membrane and preparation method thereof

By forming a biomass nanofiber intermediate layer on the hydrophilic substrate of the nanofiltration membrane and performing interfacial polymerization, the problem of low charge density on the surface of the existing nanofiltration membrane is solved, and the preparation of a high negative charge nanofiltration membrane is realized, with low Zeta potential, high permeability and high ion separation efficiency, and the production cost is reduced.

CN119926184APending Publication Date: 2025-05-06NANJING UNIV

Patent Information

Application Number
CN202510341586.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

The surface charge density of existing nanofiltration membranes is low, resulting in low permeability, low ion separation efficiency, and high production costs.

Method used

By modifying the substrate with an organic solvent, a hydrophilic substrate is prepared and the biomass raw material is strengthened and oxidized to form a biomass nanofiber intermediate layer, and then an interfacial polymerization reaction is carried out on its surface to form a polyamide active layer with a surface Zeta potential below -90mV.

Benefits of technology

The preparation of a high negative charge nanofiltration membrane is achieved, with low Zeta potential, high permeability and high ion separation efficiency, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119926184A_ABST
    Figure CN119926184A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-negative-electricity nanofiltration membrane, which comprises the following steps: step 1, modifying a substrate by using an organic solvent to obtain a hydrophilic substrate; step 2, performing enhanced oxidation treatment on the biomass raw material to obtain biomass nanofibers carrying oxygen-containing functional groups, and depositing the biomass nanofibers on the surface of the hydrophilic substrate to form a biomass nanofiber middle layer; the enhanced oxidation treatment is one or more of oxidant coupling acid treatment, alkali treatment and cell disrupter ultrasonic treatment; the usage amount of the oxidizing agent is 5-50 wt%; and 3, carrying out interfacial polymerization reaction on a polyamine monomer and an acyl chloride monomer on the surface of the biomass nanofiber intermediate layer to prepare the polyamide active layer with the surface Zeta potential lower than-90mV. The high-negative-electricity nanofiltration membrane obtained by the invention has low Zeta potential, high permeability and high ion separation efficiency; the surface of the high-negative-electricity nanofiltration membrane can enhance the Donnan repulsive effect, and the hydrophilicity of the surface of the membrane is improved through a carboxyl-rich structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nanofiltration membrane and a preparation method thereof, in particular to a high negative charge nanofiltration membrane and a preparation method thereof. Background Art

[0002] As a separation technology between ultrafiltration and reverse osmosis, nanofiltration membrane has shown important application value in water treatment, chemical separation, biomedicine and other fields due to its high efficiency and low energy consumption. Its separation mechanism mainly relies on the pore size screening effect and the Donnan effect of surface charge, especially for the selective retention of organic matter and multivalent ions with a molecular weight of 200-1000Da. In recent years, with the aggravation of water shortage and environmental pollution problems, the application demand of nanofiltration membrane in seawater desalination pretreatment, heavy metal wastewater treatment, drug molecule purification and other fields has continued to grow.

[0003] In a typical nanofiltration membrane synthesis, polyamine monomers and acyl chloride monomers undergo interfacial polymerization (IP) reactions in two immiscible phases to form a polyamide active layer. However, millisecond-scale polycondensation reactions make it challenging to adjust the nanostructure. Therefore, nanofiltration membranes are subject to an inherent trade-off between permeability and solute selectivity. In recent years, researchers have overcome the trade-off limitations by improving the uniformity of pore structure, reducing the thickness of the polyamide layer, and increasing the permeation area. However, due to the disordered distribution of amine and carboxyl groups during the formation of the polyamide layer, the charge density, which is an important component of the nanofiltration nanofluid transport model, has not been precisely controlled, and the generated polyamide layer often has problems such as uneven surface charge distribution and low effective charge density. For example, CN 118649567A, CN118437151A, and CN108355498A all disclose an interfacial polymerization process based on piperazine and trimesoyl chloride. Although a separation layer with a certain charge density can be formed, the absolute value of the Zeta potential on the membrane surface is less than 40 mV, resulting in a low resistance to high-valent ions (such as SO4 2- ) has a retention rate of less than 95%. In addition, the retention effect of the polyamide layer is related to compatibility and mechanical strength. The weak compatibility of inorganic materials will lead to a significant decrease in membrane separation performance. Patent CN110026094A enhances the mechanical properties of the polyamide layer by introducing nano-silicon dioxide, but nanoparticles are prone to cause membrane surface defects, which in turn reduces the separation accuracy.

[0004] In order to improve the surface charge density, the existing technology mostly adopts chemical modification or physical adsorption strategies. For example, CN118437151A proposes to post-treat the membrane surface with polyphenols and quaternary ammonium salts, and impart positive charge characteristics by protonation of amino groups, but this type of physical adsorption method has the problem of poor charge stability, and functional groups are prone to fall off under long-term operation or extreme pH conditions. Another type of technology, such as CN118594296A, uses ultrasonic atomization of sulfonic acid functionalized silicone to introduce sulfonic acid groups on the membrane surface to enhance negative charge, but this method is complex and difficult to promote on a large scale. In addition, the increase in charge density is often at the expense of membrane flux. For example, although the layer-by-layer self-assembly technology can accurately control the surface charge, the densification of the multilayer structure will cause the water flux to drop by more than 50% (Environ. Sci. Technol. 2021, 55: 738-748), which is difficult to take into account the high-throughput requirements of industry.

[0005] In general, the Zeta potential of existing nanofiltration membranes needs to be further reduced, the permeability is low, the ion separation efficiency is low, and the production cost is high. Summary of the invention

[0006] Purpose of the invention: In order to overcome the defects of the prior art, the purpose of the present invention is to provide a method for preparing a highly negatively charged nanofiltration membrane with low production cost. Another purpose of the present invention is to provide a highly negatively charged nanofiltration membrane with good hydrophilicity, low Zeta potential, high permeability and high ion separation efficiency.

[0007] Technical solution: The method for preparing a highly negatively charged nanofiltration membrane of the present invention comprises the following steps:

[0008] Step 1, modifying the substrate using an organic solvent to obtain a hydrophilic substrate;

[0009] Step 2, the biomass raw material is subjected to enhanced oxidation treatment to obtain biomass nanofibers carrying oxygen-containing functional groups, which are deposited on the surface of a hydrophilic substrate to form a biomass nanofiber intermediate layer; the enhanced oxidation treatment is one or more of oxidant-coupled acid treatment, alkali treatment, and cell disruptor ultrasonic treatment; the amount of the oxidant is 5 to 50 wt%;

[0010] Step 3: The polyamine monomer and the acyl chloride monomer undergo an interfacial polymerization reaction on the surface of the biomass nanofiber intermediate layer to obtain a polyamide active layer with a surface Zeta potential lower than -90 mV.

[0011] Furthermore, in step 1, the organic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol. The substrate is one or more of polyethersulfone microfiltration membrane, polysulfone microfiltration membrane, polyvinylidene fluoride microfiltration membrane, cellulose acetate microfiltration membrane, and nylon microfiltration membrane.

[0012] Furthermore, in step 2, the biomass raw material is one or more of woody plants, herbaceous plants, animal tunicates, algae plants, and microbial aggregates.

[0013] Furthermore, in step 2, the oxidant is selected from one or more of 2,2,6,6-tetramethylpiperidine-N-oxyl free radical, sodium hypochlorite, sodium chlorite, sodium bromide, and hydrogen peroxide. The mass ratio of 2,2,6,6-tetramethylpiperidine-N-oxyl free radical to other oxidants is 1:5 to 90. The oxygen-containing functional groups include carboxyl and hydroxyl groups, and the oxygen element of the oxygen-containing functional groups accounts for 40% to 60% of the total element content.

[0014] Furthermore, in step three, the polyamine monomer is one or more of piperazine, m-phenylenediamine, ethylenediamine, hexamethylenediamine, and thiourea, and the acyl chloride monomer is one or more of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride.

[0015] Furthermore, in step three, the mass percentage of the polyamine monomer is 0.02-0.2 wt %, the mass volume ratio of the acyl chloride monomer is 0.01-0.1 w / v %, and the interfacial polymerization reaction time is 5 s-10 min.

[0016] The high negative charge nanofiltration membrane of the present invention comprises, from bottom to top, a hydrophilic substrate, a biomass nanofiber intermediate layer and a polyamide active layer; the surface Zeta potential of the polyamide active layer at pH 7 is -96 to -148 mV.

[0017] Preparation principle: The intermediate layer of biomass nanofibers accelerates the conversion of hydroxyl groups to carboxyl groups in nanofibers by coupling acid / base / ultrasonic treatment with optimized oxidant components, and introduces the electrostatic attraction between carboxyl groups and amino groups in addition to the hydrogen bond interaction between the hydroxyl groups of biomass nanofibers and the amino groups of polyamine monomers, thereby enhancing the interaction between the two. The enhanced interaction reduces the reaction kinetics of interfacial polymerization and forms a uniform initial layer at the interface of the water phase-oil phase. The directional initial layer prevents further penetration of the polyamine monomers, constructs a low cross-linking / acyl chloride monomer terminal structure on the front surface of the polyamide, and produces a highly negatively charged nanofiltration membrane.

[0018] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0019] 1 The obtained highly negatively charged nanofiltration membrane has low Zeta potential, high permeability and high ion separation efficiency;

[0020] 2. The highly negatively charged nanofiltration membrane surface can enhance the Donnan exclusion effect, and the carboxyl-rich structure improves the hydrophilicity of the membrane surface, thereby significantly improving the separation effect of the obtained highly negatively charged nanofiltration membrane on monovalent / divalent anions;

[0021] 3. The present invention is based on green biomass raw materials to prepare a biomass nanofiber intermediate layer and then synthesize a nanofiltration membrane. Biomass is easily available and sustainable, which reduces the production cost of the nanofiltration membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 are scanning electron microscope images of the intermediate layer of biomass nanofibers obtained in Examples 1 to 5 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, and (e) is Example 5;

[0023] Figure 2 are scanning electron microscope images of polyamide active layers obtained in Examples 1 to 5 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, and (e) is Example 5;

[0024] Figure 3 are transmission electron microscope images of the highly negatively charged nanofiltration membranes obtained in Examples 1 to 5 of the present invention, wherein (a) is Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 4, and (e) is Example 5;

[0025] Figure 4 It is the membrane surface Zeta potential diagram of the highly negatively charged nanofiltration membrane obtained in Examples 1 to 5 of the present invention;

[0026] Figure 5 This is a comparison chart of the salt solution retention performance of the high negative charge nanofiltration membranes obtained in Examples 1 to 5 of the present invention;

[0027] Figure 6 It is the membrane surface Zeta potential diagram of the highly negatively charged nanofiltration membrane obtained in Examples 7 to 9 of the present invention;

[0028] Figure 7 is a scanning electron microscope image of the nanofiltration membrane obtained in Comparative Example 1;

[0029] Figure 8 This is the Zeta potential diagram of the membrane surface of the nanofiltration membrane obtained in Comparative Example 1;

[0030] Fig. 9 This is a scanning electron microscope image of the nanofiltration membrane obtained in Comparative Example 2;

[0031] Fig.10 This is the Zeta potential diagram of the membrane surface of the nanofiltration membrane obtained in Comparative Example 2. DETAILED DESCRIPTION

[0032] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0033] Example 1

[0034] A method for preparing a highly negatively charged nanofiltration membrane comprises the following steps:

[0035] S1. A polyethersulfone microfiltration membrane with a pore size of 0.22 μm was pre-immersed in a polar organic solvent, isopropanol, for 10 min, and the resulting hydrophilic substrate was subsequently transferred to a vacuum filtration device.

[0036] S2, the selected biomass is the tunicate of sea squirt. 10g of dried tunicate raw material is treated with 5wt% sodium hydroxide solution at 50℃ for 3h, and then treated with 5wt% of digestion agent sodium hypochlorite (using 3molL -1 Acetic acid adjusts pH to 4.5) and treats at 80°C for 3h to digest impurities on the surface of the capsule. Repeat this process several times until a white flaky product is obtained. Weigh 1g of white substance in a beaker, add 100mL of 1wt% 2,2,6,6-tetramethylpiperidine-N-oxyl free radical and 9wt% sodium hypochlorite mixed solution for enhanced oxidation, and adjust the pH to 10 with NaOH solution. Place in a temperature-controlled stirrer and oxidize at 60°C for 48h, rinse with ultrapure water, and suspend in 200mL ultrapure water. Use a wall breaker to break up the suspension, use a 20kHz cell disruptor to ultrasonicate at 400W for 6h, stop for 8s every 10s of ultrasonication, and prepare a 9mg / L capsule nanofiber dispersion for standby use. The oxygen content of the obtained capsule nanofiber is 41.4%. Take 5mL of the capsule nanofiber dispersion and deposit it on a hydrophilic substrate, dry it at room temperature for 10min, and obtain the capsule nanofiber intermediate layer.

[0037] S3. Pour 20 mL of 0.05 w / v% piperazine aqueous solution on the surface of the capsule nanofiber / polyethersulfone composite membrane and soak for 2 minutes to make the piperazine evenly distributed. After removing the piperazine aqueous solution, dry for 4 minutes, add 20 mL of 0.04 w / v% trimesoyl chloride solution again for interfacial polymerization reaction for 1 minute, and remove the excess solution. The obtained membrane is placed in a 60°C blower dryer and heated for 15 minutes, and soaked in ultrapure water overnight to obtain a high negative charge nanofiltration membrane.

[0038] Example 2

[0039] The remaining steps of this embodiment are the same as those of embodiment 1, with the only difference being that in step S2, 9wt% sodium hypochlorite is replaced by 9wt% sodium chlorite, and the oxygen content of the obtained encapsulated nanofibers is 40.9%, thereby obtaining a highly negatively charged nanofiltration membrane.

[0040] Example 3

[0041] The remaining steps of this embodiment are the same as those of embodiment 1, with the only difference being that in step S2, 9wt% sodium hypochlorite is replaced by 9wt% sodium bromide, the oxygen content of the obtained biomass nanofibers is 46.5%, and a highly negatively charged nanofiltration membrane is obtained.

[0042] Example 4

[0043] The remaining steps of this embodiment are the same as those of Embodiment 1, with the only difference being that in step S2, 9wt% sodium hypochlorite is replaced by 4wt% sodium hypochlorite and 5wt% sodium chlorite, and the oxygen content of the obtained biomass nanofibers is 48.1%, thereby obtaining a highly negatively charged nanofiltration membrane.

[0044] Example 5

[0045] The remaining steps of this embodiment are the same as those of Embodiment 1, with the only difference being that in step S2, 9wt% sodium hypochlorite is replaced by 4wt% sodium hypochlorite and 5wt% sodium bromide, and the oxygen content of the obtained biomass nanofibers is 52.4%, thereby obtaining a highly negatively charged nanofiltration membrane.

[0046] Table 1 Different oxidants and proportions of Examples 1 to 5

[0047] Nanofiltration membrane Oxidants Oxidant ratio Example 1 2,2,6,6-Tetramethylpiperidinyl-N-oxyl Free Radical and Sodium Hypochlorite 1:9 Example 2 2,2,6,6-Tetramethylpiperidinyl-N-oxyl Free Radical and Sodium Chlorite 1:9 Example 3 2,2,6,6-Tetramethylpiperidinyl-N-oxyl free radical and sodium bromide 1:9 Example 4 2,2,6,6-Tetramethylpiperidinyl-N-oxyl radical, sodium hypochlorite and sodium chlorite 1:4:5 Example 5 2,2,6,6-Tetramethylpiperidinyl-N-oxide free radical, sodium hypochlorite and sodium bromide 1:4:5

[0048] The middle layer ( Figure 1 ) and its surface polyamide active layer ( Figure 2 ) to analyze the surface morphology. The results showed that the composite nanofiltration membrane is composed of a hydrophilic substrate, an encapsulated nanofiber intermediate layer and a polyamide active layer. The intermediate layer has a flat and evenly distributed morphology and can completely cover the polyethersulfone pores. The polyamide active layer has a complete morphology, a smooth surface and low roughness. The thickness of the biomass nanofiber intermediate layer and the polyamide active layer was measured by transmission electron microscopy. Figure 3 As shown, the results show that the thickness of the biomass nanofiber intermediate layer is about 20-50 nm, and the thickness of the polyamide active layer is about 10-20 nm. The high negative charge nanofiltration membrane obtained in Examples 1-5 has an extremely low membrane surface Zeta potential, which can reach -96 to -148 mV at pH 7. Figure 4 shown.

[0049] Example 6

[0050] Nanofiltration membrane salt solution retention performance test:

[0051] The high negative charge nanofiltration membranes obtained in Examples 1 to 5 were tested for interception performance, and the specific methods are as follows:

[0052] (1) The separation performance of the nanofiltration membrane was tested using a cross-flow filtration device. The effective filtration membrane area was 7.07 cm 2In order to stabilize the pressure during the test, the composite nanofiltration membrane was pre-pressurized with pure water at 6 bar for 1 h at room temperature.

[0053] (2) Pure water permeation: Under room temperature and 4 bar conditions, an ultrapure water cross-flow filtration device was used to operate for 2 h, and the pure water effluent volume of the nanofiltration membrane obtained in Examples 1 to 5 was collected to calculate the pure water permeation.

[0054] (3) Separation factor: A mixed salt solution containing 1 g / L Na2SO4 and 1 g / L NaCl was prepared. The cross-flow filtration device was operated for 2 h at room temperature and 4 bar. The SO4 in the inlet and outlet water was determined using ion chromatography. 2- , Cl - concentration, and thus the monovalent / divalent anion separation coefficient is calculated, that is, Test results such as Figure 5 shown.

[0055] It can be seen that the composite nanofiltration membranes obtained in Examples 1 to 5 of the present invention have excellent permeability and Cl - / SO4 2- The separation capacity can effectively overcome the trade-off limit. Calculate the nanofiltration membrane obtained in Examples 1 to 5 of the present invention The high separation factors indicate that the highly negatively charged nanofiltration membrane can significantly enhance the Donnan exclusion effect, thereby achieving effective screening of monovalent and divalent anions.

[0056] Among the above embodiments, the best embodiment is Embodiment 5.

[0057] Example 7

[0058] A method for preparing a highly negatively charged nanofiltration membrane comprises the following steps:

[0059] S1. A nylon microfiltration membrane with a pore size of 0.22 μm is pre-immersed in a polar organic solvent, isopropanol, for 10 min, and the resulting hydrophilic substrate is then transferred to a vacuum filtration device. Isobutanol can also be replaced by any one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.

[0060] S2. The selected biomass is eucalyptus pulp with a content of about 27%. 1g of eucalyptus pulp was weighed in a beaker, and 100mL of a mixed solution of 3wt% 2,2,6,6-tetramethylpiperidine-N-oxyl free radical and 30wt% sodium hypochlorite was added for enhanced oxidation, and the pH was adjusted to 10 with a NaOH solution. After being placed in a temperature-controlled agitator and oxidized at 60°C for 48h, it was rinsed with ultrapure water and suspended in 200mL ultrapure water. The suspension was broken up by a wall breaker, and ultrasonicated at 400W for 6h with a 20kHz cell disruptor, and stopped for 8s every 10s of ultrasonication to obtain a eucalyptus nanofiber dispersion with a concentration of 9mg / L for standby use. The oxygen content of the obtained eucalyptus nanofibers was 43.7%. 5mL of eucalyptus nanofiber dispersion was deposited on a hydrophilic substrate and dried at room temperature for 10min to obtain a eucalyptus nanofiber intermediate layer.

[0061] S3, pour 20mL, 0.02wt% m-phenylenediamine aqueous solution on the surface of eucalyptus nanofiber / polyethersulfone composite membrane and soak for 2min to make m-phenylenediamine evenly distributed. After removing the m-phenylenediamine aqueous solution, dry for 4min, add 20mL, 0.01w / v% terephthaloyl chloride solution again for interfacial polymerization reaction for 1min, and remove excess solution. The obtained membrane is placed in a 60℃ blower dryer and heated for 15min, and soaked in ultrapure water overnight to obtain a high negative charge nanofiltration membrane.

[0062] Example 8

[0063] A method for preparing a highly negatively charged nanofiltration membrane comprises the following steps:

[0064] S1. A polyvinylidene fluoride microfiltration membrane with a pore size of 0.22 μm was pre-immersed in a polar organic solvent ethanol for 10 min, and the resulting hydrophilic substrate was then transferred to a vacuum filtration device.

[0065] S2. The selected biomass is a bacterial cellulose aggregate with a content of about 40%. 1g of bacterial cellulose aggregate was weighed in a beaker, and 100mL of a mixed solution of 1wt% 2,2,6,6-tetramethylpiperidine-N-oxyl free radical and 9wt% sodium hypochlorite was added for enhanced oxidation, and the pH was adjusted to 10 with a NaOH solution. After being oxidized at 60°C for 48h in a temperature-controlled agitator, it was rinsed with ultrapure water and suspended in 200mL of ultrapure water. The suspension was broken up by a wall breaker, and ultrasonicated at 400W for 6h with a 20kHz cell disruptor, and stopped for 8s every 10s of ultrasonication to obtain a bacterial cellulose nanofiber dispersion with a concentration of 9mg / L for standby use. 5mL of bacterial cellulose nanofiber dispersion was deposited on a hydrophilic substrate and dried at room temperature for 10min to obtain a bacterial cellulose nanofiber intermediate layer.

[0066] S3. Pour 20 mL of 0.2 wt% ethylenediamine aqueous solution on the surface of bacterial cellulose nanofiber / polyethersulfone composite membrane and soak for 2 minutes to make the ethylenediamine evenly distributed. After removing the ethylenediamine aqueous solution, dry for 4 minutes, add 20 mL of 0.1 w / v% isophthaloyl chloride solution again to react for 1 minute, and remove the excess solution. The obtained membrane is placed in a 60°C blower dryer and heated for 15 minutes, and soaked in ultrapure water overnight to obtain a high negative charge nanofiltration membrane. Ethylenediamine can be replaced by hexamethylenediamine.

[0067] Example 9

[0068] A method for preparing a highly negatively charged nanofiltration membrane comprises the following steps:

[0069] S1. A cellulose acetate microfiltration membrane with a pore size of 0.2 μm was pre-immersed in a polar organic solvent, n-propanol, for 10 min, and the resulting hydrophilic substrate was then transferred to a vacuum filtration device.

[0070] S2, the selected biomass is corn stalks, 10g of dried corn stalks raw material was treated with 5wt% sodium hydroxide solution at 50℃ for 3h, and then 5wt% of the digester sodium hypochlorite (3molL -1 Acetic acid was used to adjust the pH to 4.5) and treated at 80 ° C for 3 hours to digest the impurities on the surface of corn stalks. Repeat this process several times until a white flaky product is obtained. Weigh 1g of white substance in a beaker, add 100mL of 1wt% 2,2,6,6-tetramethylpiperidine-N-oxyl free radical and 4wt% sodium chlorite mixed solution for enhanced oxidation, and adjust the pH to 10 with NaOH solution. After being placed in a temperature-controlled stirrer and oxidized at 60 ° C for 48 hours, it was rinsed with ultrapure water and suspended in 200mL ultrapure water. The suspension was broken by a wall breaker, and ultrasonicated at 400W for 6 hours with a 20kHz cell disruptor, and stopped for 8 seconds every 10 seconds to obtain a corn stalk nanofiber dispersion with a concentration of 9mg / L for standby use. Take 5mL of corn stalk nanofiber dispersion and deposit it on a hydrophilic substrate, dry it at room temperature for 10 minutes, and obtain a corn stalk nanofiber intermediate layer.

[0071] S3. Pour 20 mL of 0.1 wt% thiourea aqueous solution on the surface of corn straw nanofiber / polyethersulfone composite membrane and soak for 2 min to make the thiourea evenly distributed. After removing the thiourea aqueous solution, dry for 4 min, add 20 mL of 0.05 w / v% phthaloyl chloride solution again to react for 1 min, and remove the excess solution. The obtained membrane is placed in a 60°C blower dryer and heated for 15 min, and soaked in ultrapure water overnight to obtain a high negative charge nanofiltration membrane.

[0072] The surface Zeta potential of the highly negatively charged nanofiltration membranes obtained in Examples 7 to 9 is as follows: Figure 6At pH 7, the surface Zeta potentials of the membranes of Examples 7 to 9 were as high as -94.1 mV, -113.6 mV, and -99.4 mV, respectively.

[0073] Comparative Example 1

[0074] This comparative example aims to explore the effect of the type of intermediate layer on the membrane structure.

[0075] Referring to the method of Example 1, the polyethersulfone membrane was pre-immersed in isopropanol for 10 minutes, and the obtained hydrophilic substrate was subsequently transferred to a vacuum filtration device. 5mL of 9mg / L single-walled carbon nanotube dispersion was deposited on the hydrophilic substrate and dried at room temperature for 10 minutes to obtain a single-walled carbon nanotube intermediate layer. 20mL of 0.05wt% piperazine aqueous solution was poured into the surface of the single-walled carbon nanotube / polyethersulfone composite membrane and soaked for 2 minutes to make the piperazine evenly distributed. After removing the piperazine aqueous solution, it was dried for 4 minutes, and 20mL of 0.04w / v% benzyl chloride solution was added again for interfacial polymerization reaction for 1 minute, and the excess solution was removed. The obtained membrane was placed in a 60°C blower dryer and heated for 15 minutes, and soaked in ultrapure water overnight to obtain a nanofiltration membrane.

[0076] The morphology and Zeta potential of nanofiltration membranes are as follows: Figure 7-Figure 8 As shown, scanning electron microscopy showed that the membrane surface was intact and free of defects, but the membrane surface Zeta potential at pH 7 was only -27 mV.

[0077] Comparative Example 2

[0078] This comparative example aims to explore the effect of organic solvents on membrane structure.

[0079] Referring to the method of Example 1, the selected biomass is the tunicate of sea squirt. 10 g of dried tunicate raw material is treated with 5 wt % sodium hydroxide solution at 50° C. for 3 h, and then treated with 5 wt % sodium chlorite solution (using 3 mol L -1 The suspension was treated at 80°C for 3h with acetic acid (pH adjusted to 4.5). The process was repeated several times until a white flaky product was obtained. 1g of white substance was weighed in a beaker, 100mL of 10wt% oxidant solution was added, and the pH was adjusted to 10 with NaOH solution. After oxidation at 60°C for 48h in a temperature-controlled agitator, it was rinsed with ultrapure water and suspended in 200mL of ultrapure water. The suspension was broken up with a wall breaker, and ultrasonicated at 400W for 6h with a 20kHz cell disruptor, with 8s pause for every 10s of ultrasonication, to obtain a 9mg / L capsule nanofiber dispersion for standby use.

[0080] Take 5mL of the tufted nanofiber dispersion and deposit it on an untreated polyethersulfone substrate, and dry it at room temperature for 10 minutes to obtain a tufted nanofiber middle layer. Pour 20mL of a 0.05wt% piperazine aqueous solution on the surface of the tufted nanofiber / polyethersulfone composite membrane and soak it for 2 minutes to make the piperazine evenly distributed. After removing the piperazine aqueous solution, dry it for 4 minutes, add 20mL of a 0.04w / v% benzyl chloride solution again to perform interfacial polymerization for 1 minute, and remove the excess solution. The resulting membrane is placed in a 60℃ blower dryer and heated for 15 minutes, and soaked in ultrapure water overnight to obtain a nanofiltration membrane.

[0081] The morphology and Zeta potential of nanofiltration membranes are as follows: Figure 9-10 As shown, scanning electron microscopy shows that defects are easily generated on the membrane surface. Although the membrane surface Zeta potential at pH 7 is -104mV, it is unable to effectively intercept salt ions.

Claims

1. A method for preparing a highly negatively charged nanofiltration membrane, characterized in that: The following steps are involved: Step 1, modifying the substrate using an organic solvent to obtain a hydrophilic substrate; Step 2, the biomass raw material is subjected to enhanced oxidation treatment to obtain biomass nanofibers carrying oxygen-containing functional groups, which are deposited on the surface of a hydrophilic substrate to form a biomass nanofiber intermediate layer; the enhanced oxidation treatment is one or more of oxidant-coupled acid treatment, alkali treatment, and cell disruptor ultrasonic treatment; the amount of the oxidant is 5 to 50 wt%; Step 3: The polyamine monomer and the acyl chloride monomer undergo an interfacial polymerization reaction on the surface of the biomass nanofiber intermediate layer to obtain a polyamide active layer with a surface Zeta potential lower than -90 mV.

2. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 1, the organic solvent is one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol.

3. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 1, the substrate is one or more of a polyethersulfone microfiltration membrane, a polysulfone microfiltration membrane, a polyvinylidene fluoride microfiltration membrane, a cellulose acetate microfiltration membrane, and a nylon microfiltration membrane.

4. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 2, the biomass raw material is one or more of woody plants, herbaceous plants, animal tunicates, algae plants, and microbial aggregates.

5. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 2, the oxidant is selected from one or more of 2,2,6,6-tetramethylpiperidine-N-oxyl free radical, sodium hypochlorite, sodium chlorite, sodium bromide, and hydrogen peroxide.

6. The method for preparing a highly negatively charged nanofiltration membrane according to claim 5, characterized in that: In the step 2, the mass ratio of 2,2,6,6-tetramethylpiperidinyl-N-oxyl free radical to other oxidants is 1:5-90.

7. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 2, the oxygen-containing functional groups include carboxyl and hydroxyl groups, and the oxygen element in the oxygen-containing functional groups accounts for 40% to 60% of the total element content.

8. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 3, the polyamine monomer is one or more of piperazine, m-phenylenediamine, ethylenediamine, hexamethylenediamine, and thiourea, and the acyl chloride monomer is one or more of trimesoyl chloride, terephthaloyl chloride, isophthaloyl chloride, and phthaloyl chloride.

9. The method for preparing a highly negatively charged nanofiltration membrane according to claim 1, characterized in that: In the step 3, the mass percentage of the polyamine monomer is 0.02-0.2 wt %, the mass volume ratio of the acyl chloride monomer is 0.01-0.1 w / v %, and the interfacial polymerization reaction time is 5 s-10 min.

10. A highly negatively charged nanofiltration membrane obtained by the method for preparing a highly negatively charged nanofiltration membrane according to any one of claims 1 to 9, characterized in that: The invention comprises, from bottom to top, a hydrophilic substrate, a biomass nanofiber middle layer and a polyamide active layer; the surface Zeta potential of the polyamide active layer at pH 7 is -96 to -148 mV.

Citation Information

Patent Citations

  • Composite nanofiltration membrane with negative electric charges and preparation method of composite nanofiltration membrane

    CN108355498A

  • Preparation method of high-flux anti-pollution in-situ silicon dioxide / polyamide reverse osmosis nanometer composite membrane

    CN110026094A

  • Cationic screening nanofiltration membrane based on negatively charged hyperbranched polyamide and preparation method

    CN118437151A

  • Preparation method and application of sulfo group functionalization modified organic silicon composite film

    CN118594296A

  • Application of polyamide nanofiltration membrane to selective separation of new pollutants and salt ions in water environment

    CN118649567A

Cited By

  • High-permeability-selectivity strong-electronegativity nanofiltration membrane as well as preparation method and application thereof

    CN121130683A

  • A high-permeability selective strong negative nanofiltration membrane, a preparation method and application thereof

    CN121130683B